From Zircon Sand to Advanced Functional Materials: Synthesis and Characterization of Zirconium-Based Metal Organic Frameworks - Palapessy, Berryl Vendo; Reda, Brilyan Muhammad Rasyid; Failamani, Fainan; Patah, Aep (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
This study presents an integrated approach for converting zircon sand into functional materials based on zirconium metal–organic frameworks (Zr-MOFs). Zirconium was extracted through three main steps: alkali fusion, water leaching, and nitric acid leaching, resulting in a precursor identified as Zr(OH)2(NO3)2·1.33H2O (ZON). Characterization using XRF, FTIR, XRD, and SEM-EDX revealed that ZON possesses a high zirconium content (94.87% relative to the total metal content) and distinct structural features. The ZON compound was subsequently utilized as a novel precursor in synthesizing of three types of Zr-MOFs: UiO-66, MOFs-801, and MOFs-808. Structural and morphological analyses indicated that all three MOFs were successfully formed with high crystallinity. These findings demonstrate that locally sourced zircon sand has strong potential as a sustainable and cost-effective raw material for MOF synthesis, while also bridging the knowledge gap between zirconium extraction and the development of sustainable materials chemistry based on local mineral resources.